NUR-MUHAMMAD AL-AWARI AND A CRITIQUE OF IMAM GAZI-MUHAMMAD’S VIEWS AND ACTIONS IN A MANUSCRIPT OF HIS WORKS: A SOURCE-STUDY ANALYSIS - Musaev, Mahac Abdulaevic (History, Archeology and Ethnography of the Caucasus, 2024)
The archive of the Institute of History, Archeology, and Ethnography of the Dagestan Federal Research Center of the Russian Academy of Sciences houses an Arabic manuscript – a small notebook comprising 20 pages. M.-S.D.  Saidov attributes this manuscript to Nur-Muhammad al-Awari’s legal opinions (taqrirat), wherein he critiques the work (risala) “Iqamat al-Burhan li-irtidad ‘urafa’ Dagistan” (“The Establishment of an Argument Regarding the Apostasy of the Dagestan Nobility”) authored by the first Imam of Dagestan, Gazi-Muhammad al-Gimrawi. Saidov also dates the manuscript to the first half of the 1830s. An examination of the manuscript reveals that its content belongs to the aforementioned qadi of the Avar Khanate, Nur-Muhammad, in which he opposes the ideas and actions of Imam Gazi-Muhammad al-Gimrawi. Nur-Muhammad criticizes Gazi-Muhammad’s interpretations regarding the imam’s authority, takfir, jihad, and hijra. His legal opinions draw upon a wide range of sources, primarily classical works of Shaf’i jurisprudence. The manuscript is an incomplete work. It contains at least two messages from al-Awari addressed to al-Gimrawi, intended for dispatch. The text of the first message spans pages 1-8 and dates prior to 1830. The second part of the manuscript (pp. 9–20) should be attributed to a later period, with the concluding pages dated to 1831. The paper is prefaced with a biography of Nur-Muhammad, illuminating that his legal stance may stem not only from his theological views but also from his role as the qadi of the Avar Khanate, who stood in opposition to Imam Gazi-Muhammad.
Keywords: Nur-Muhammad al-Awari; Imam Gazi-Muhammad; Avar khanate; Caucasian imamate